A biological modelling based comparison of radiotherapy plan robustness using photons vs protons for focal prostate boosting. (April 2018) - Pedersen, Jesper; Casares-Magaz, Oscar; Petersen, Jørgen B.B.; Rørvik, Jarle; Bentzen, Lise; Andersen, Andreas G.; Muren, Ludvig P.
Abstract: Background and purpose: Focal tumour boosting is currently explored in radiotherapy of prostate cancer to increase tumour control. In this study we applied dose response models for both tumour control and normal tissue complications to explore the benefit of proton therapy (PT) combined with focal tumour boosting, also when accounting for inter-fractional motion. Materials and methods: CT scans of seven patients fused with MRI-based index volumes were used. Two volumetric modulated arc therapy (VMAT) plans were created for each patient; one with conventional dose (77 Gy) to the entire prostate, and one with an additional integrated boost (total dose of 95 Gy) to the index lesion. Two corresponding intensity modulated PT (IMPT) plans were created using two lateral opposing spot scanning beams. All plans were evaluated using an MRI-based tumour control probability (TCP) model and normal tissue complication probability (NTCP) models for the rectum and bladder. Plan robustness was evaluated using dose re-calculations on repeat cone-beam CTs. Results: Across all plans, median TCP increased from 86% (range: 59–98%) without boost to 97% (range: 96–99%) with boost. IMPT plans had lower rectum NTCPs (e.g. 3% vs. 4% for boost plans) but higher bladder NTCPs (20% vs. 18% for boost plans), yet only the bladder NTCPs remained different in the cone beam CT-based re-calculations. Conclusions: Focal tumour boosting can be delivered with either VMAT or protons, and increases the predicted TCP. The small benefit of IMPT when assessing the planned dose distributions was lost when accounting for inter-fractional motion.